2014
DOI: 10.1002/lary.24809
|View full text |Cite
|
Sign up to set email alerts
|

Triple-layered polyurethane prosthesis with wrinkles for repairing partial tracheal defects

Abstract: NA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Polyethylene terephthalate (PET) and polyurethane (PU) are FDA-approved polymers that have been used in humans for tracheal tissue engineering. [4][5][6]13 Using a lamb model, we demonstrated that seeding a PET + PU scaffold with autologous bone marrow-derived mononuclear cells (BM-MNC) attenuates stenosis and accelerates epithelialization. 8 However, graft stenosis resulting in airway obstruction is seen in all cases and must be managed with endoscopic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Polyethylene terephthalate (PET) and polyurethane (PU) are FDA-approved polymers that have been used in humans for tracheal tissue engineering. [4][5][6]13 Using a lamb model, we demonstrated that seeding a PET + PU scaffold with autologous bone marrow-derived mononuclear cells (BM-MNC) attenuates stenosis and accelerates epithelialization. 8 However, graft stenosis resulting in airway obstruction is seen in all cases and must be managed with endoscopic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchoscopy using a rigid 4-mm 0 endoscope (Karl Storz, Tuttlingen, Germany) was performed at 2, 4, 6 and 8 weeks postoperatively (post implantation). The inner surface of the scaffold-grafted areas was examined, and we determined the following [4,7]: (1) narrowing of the lumen, (2) re-epithelization, (3) formation of granulation tissue around the scaffoldgrafted area and (4) integration of the implanted scaffolds. Degree of stenosis was classified on a four-point scale: 0-10%, no narrowing noted; 11-50%, mild narrowing; 51-70%, moderate narrowing; and >71%, severe narrowing.…”
Section: Bronchoscopymentioning
confidence: 99%
“…Partial reconstruction of a human airway with a tissue-engineered prosthesis was successfully performed by Omori et al [6] in 2002. In addition, many types of artificial tracheal patches for partial reconstruction have shown satisfactory experimental results [4,7,8]. In contrast, a circumferential or total reconstruction of trachea is more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene terephthalate (PET) and polyurethane (PU), which are both FDA-approved polymers, have both been explored in combination and in isolation. [31][32][33] Modification of the PET/PU ratios can result in biomechanical characteristics similar to native trachea. The PET-only grafts demonstrated greater seeded cell retention, but both constructs demonstrated viability in vivo.…”
Section: Scaffoldsmentioning
confidence: 99%